Sosialisasi Pembuatan Laporan Keuangan Klub pada Klub Bulutangkis di PB Tanjung Mas - Akhmad Suyono (Jurnal Abdimas Multidisiplin, 2022)
Purpose: To provide knowledge about the importance of financial bookkeeping for the PB Tanjung Mas organization that they run, their financial records are more structured. The second goal is to increase their understanding of the process of making simple financial bookkeeping by providing some examples of economic transactions and how to solve it and the distribution of debit/credit cash books. Research methodology: The method used in carrying out the service is socialization and mentoring. before doing service, is to meet face-to-face during the championship and do a little question and answer about inflating training operational costs unexpectedly because no reports have been made. The approach that has been taken, the idea arises to overcome these problems, by organizing training and mentoring. Results: The result of this service is to provide a new experience for badminton clubs, especially PB Tanjung Mas about the importance of having simple financial reports, in order to be able to manage their respective operational costs so that there is no minus at the end of the month Limitations: This service limit is for recording daily transactions at PB Tanjung Mas and recording supply of chokechocks. Contribution: The contribution of this program is to provide knowledge about the meaning of accounting, the benefits of accounting and financial bookkeeping for traders, the accounts contained in the books, debit-credit positions, examples of transactions that often occur, to the process of journalizing and distributing debit cash books/credit to PB Tanjung Mas Tampan. The hope from the implementation of this community service program is that the club's finances become sustainable by implementing simple financial bookkeeping every period. So that the club management has a good financial record.